Library Management Strategies in Providing Reading Materials Based on Students' Needs at SMP Negeri 15 Yogyakarta - Jakina Jakina; Eny Sulistyowati (Journal of Mandalika Social Science, 2026)
This study aims to analyze library management strategies implemented by library administrators in providing reading materials that correspond to students' academic and personal needs at SMP Negeri 15 Yogyakarta. The research adopts a qualitative approach using a literature review method to examine concepts of library management, educational management, and student-centered library services. The analysis is framed through management functions, including planning, organizing, implementing, and controlling (POAC), to evaluate how library resources are managed effectively. The findings indicate that effective library management begins with systematic planning based on students' reading needs and curriculum requirements, followed by proper organization of collections, collaborative implementation involving teachers and school stakeholders, and continuous evaluation of library services. The integration of digital resources, user feedback, and reading promotion programs further strengthens library performance in supporting students' learning outcomes. The study concludes that effective management practices significantly contribute to improving library services and developing a sustainable reading culture within the school environment.